Copper-catalysed asymmetric allylic alkylation of alkylzirconocenes to racemic 3,6-dihydro-2H-pyrans - Rideau, Emeline; Fletcher, Stephen P. (Beilstein Journal of Organic Chemistry, 2015)
Asymmetric allylic alkylation is a powerful reaction that allows the enantioselective formation of C–C bonds. Here we describe the asymmetric alkylation of alkylzirconium species to racemic 3,6-dihydro-2H-pyrans. Two systems were examined: 3-chloro-3,6-dihydro-2H-pyran using linear optimization (45–93% ee, up to 33% yield, 5 examples) and 3,6-dihydro-2H-pyran-3-yl diethyl phosphate with the assistance of a design of experiments statistical approach (83% ee, 12% yield). 1H NMR spectroscopy was used to gain insight into the reaction mechanisms.
Keywords: allylic alkylation; asymmetric catalysis; copper; design of experiments; dynamic kinetic asymmetric transformation; heterocycles; Schwartz reagent

(untitled) - Faber, K. (Chem. – Eur. J., 2001)

(untitled) - Vedejs, E.; Jure, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Mohr, J. T.; Ebner, D. C.; Stoltz, B. M. (Org. Biomol. Chem., 2007)

(untitled) - Miller, L. C.; Sarpong, R. (Chem. Soc. Rev., 2011)

(untitled) - Trost, B. M.; Bunt, R. C. (J. Am. Chem. Soc., 1994)

(untitled) - Trost, B. M.; Van Vranken, D. L. (Chem. Rev., 1996)

(untitled) - Lu, Z.; Ma, S. (Angew. Chem., Int. Ed., 2008)

(untitled) - Huerta, F. F.; Minidis, A. B. E.; Bäckvall, J.-E. (Chem. Soc. Rev., 2001)

(untitled) - Trost, B. M.; Fandrick, D. R. (Aldrichimica Acta, 2007)

(untitled) - Norinder, J.; Bäckvall, J.-E. (Chem. – Eur. J., 2007)

(untitled) - Langlois, J.-B.; Alexakis, A. (Chem. Commun., 2009)

(untitled) - Langlois, J.-B.; Alexakis, A. (Adv. Synth. Catal., 2010)

(untitled) - Katcher, M. H.; Doyle, A. G. (J. Am. Chem. Soc., 2010)

(untitled) - Hamilton, J. Y.; Hauser, N.; Sarlah, D.; Carreira, E. M. (Angew. Chem., Int. Ed., 2014)

(untitled) - Misale, A.; Niyomchon, S.; Luparia, M.; Maulide, N. (Angew. Chem., Int. Ed., 2014)

(untitled) - Ito, H.; Kunii, S.; Sawamura, M. (Nat. Chem., 2010)

(untitled) - Langlois, J.-B.; Emery, D.; Mareda, J.; Alexakis, A. (Chem. Sci., 2012)

(untitled) - Delvos, L. B.; Oestreich, M. (Synthesis, 2015)

(untitled) - Maksymowicz, R. M.; Roth, P. M. C.; Fletcher, S. P. (Nat. Chem., 2012)

(untitled) - Sidera, M.; Roth, P. M. C.; Maksymowicz, R. M.; Fletcher, S. P. (Angew. Chem., Int. Ed., 2013)

(untitled) - Maciver, E. E.; Maksymowicz, R. M.; Wilkinson, N.; Roth, P. M. C.; Fletcher, S. P. (Org. Lett., 2014)

(untitled) - Roth, P. M. C.; Fletcher, S. P. (Org. Lett., 2015)

(untitled) - Rideau, E.; Mäsing, F.; Fletcher, S. P. (Synthesis, 2015)

(untitled) - Caprioglio, D.; Fletcher, S. P. (Chem. Commun., 2015)

(untitled) - Maksymowicz, R. M.; Bissette, A. J.; Fletcher, S. P. (Chem. – Eur. J., 2015)

(untitled) - You, H.; Rideau, E.; Sidera, M.; Fletcher, S. P. (Nature, 2015)

(untitled) - Sidera, M.; Fletcher, S. P. (Chem. Commun., 2015)

(untitled) - Morken, J. P.; Didiuk, M. T.; Visser, M. S.; Hoveyda, A. H. (J. Am. Chem. Soc., 1994)

(untitled) - Fu, G. C.; Nguyen, S. T.; Grubbs, R. H. (J. Am. Chem. Soc., 1993)

(untitled) - Clark, J. S. (Chem. Commun., 2006)

(untitled) - Aggarwal, V. K.; Staubitz, A. C.; Owen, M. (Org. Process Res. Dev., 2006)

(untitled) - Weissman, S. A.; Anderson, N. G. (Org. Process Res. Dev., 2015)

(untitled) - Owen, M. R.; Luscombe, C.; Lai-Wah; Godbert, S.; Crookes, D. L.; Emiabata-Smith, D. (Org. Process Res. Dev., 2001)

(untitled) - Chen, J. J.; Nugent, T. C.; Lu, C. V.; Kondapally, S.; Giannousis, P.; Wang, Y.; Wilmot, J. T. (Org. Process Res. Dev., 2003)

(untitled) - Denmark, S. E.; Butler, C. R. (J. Am. Chem. Soc., 2008)

(untitled) - Arnold, K.; Batsanov, A. S.; Davies, B.; Whiting, A. (Green Chem., 2008)

(untitled) - Peñafiel, I.; Pastor, I. M.; Yus, M. (Eur. J. Org. Chem., 2013)

(untitled) - Harper, K. C.; Sigman, M. S. (J. Org. Chem., 2013)

(untitled) - Yoshikai, N.; Nakamura, E. (Chem. Rev., 2012)

(untitled) - Geurts, K.; Fletcher, S. P.; van Zijl, A. W.; Minnaard, A. J.; Feringa, B. L. (Pure Appl. Chem., 2008)

(untitled) - Alexakis, A.; Bäckvall, J. E.; Krause, N.; Pàmies, O.; Diéguez, M. (Chem. Rev., 2008)

(untitled) - Harutyunyan, S. R.; den Hartog, T.; Geurts, K.; Minnaard, A. J.; Feringa, B. L. (Chem. Rev., 2008)

Copper-Catalyzed Asymmetric Synthesis - Alexakis, A.; Krause, N.; Woodward, S. (Wiley-VCH, 2014)

(untitled) - Maougal, E.; Dalençon, S.; Pearson-Long, M. S. M.; Mathé-Allainmat, M.; Lebreton, J.; Legoupy, S. (Synthesis, 2014)